O Relicário de Celeida Tostes - Silva, Raquel Martins (2006)
The purpose of this thesis is to provide an outlook on plastic artist Celeida Tostes (1929-1995) and her actions at the community of Chapéu Mangueira, started in the early 1980’s. The research was developed from interviews recorded on videographic means and based on the methodology of oral history. Besides the written paper, a video-documentary was also produced. The intention of this research was to put together, from the memories of people who were familiar with the artist, a patchwork, similar to those she encouraged the women from the Chapéu Mangueira hillside shantytown to remember and to make. A parallel intention, too, was to bring up memories of what these people did together with the artist in the project 'Formation of Utilitarian Ceramic Centers in the Communities of Rio de Janeiro’s Urban Outskirts—so-called favelas' (1980-1994) and the importance it had for their lives. Furthermore, the transformations brought about by this encounter to both sides were also studied: in Chapéu Mangueira residents and in Celeida Tostes herself.